2022
DOI: 10.2196/31557
|View full text |Cite
|
Sign up to set email alerts
|

The Disparity and Dynamics of Social Distancing Behaviors in Japan: Investigation of Mobile Phone Mobility Data

Abstract: Background The availability of large-scale and fine-grained aggregated mobility data has allowed researchers to observe the dynamics of social distancing behaviors at high spatial and temporal resolutions. Despite the increasing attention paid to this research agenda, limited studies have focused on the demographic factors related to mobility, and the dynamics of social distancing behaviors have not been fully investigated. Objective This study aims to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…Previous studies suggested that mobile phone mobility was useful for observing the dynamics of physical distancing behaviors related to COVID-19 spread [49][50][51]. A study conducted in Japan reported that the mobile phone mobility of an infection-risk-exposed group was associated with the number of infections with a lag time of 0-2 days, similar to the current study [52]. They used a cross-correlation function to examine the association between the moving average of the mobility index and the time-lagged daily infected cases.…”
Section: Plos Onesupporting
confidence: 85%
“…Previous studies suggested that mobile phone mobility was useful for observing the dynamics of physical distancing behaviors related to COVID-19 spread [49][50][51]. A study conducted in Japan reported that the mobile phone mobility of an infection-risk-exposed group was associated with the number of infections with a lag time of 0-2 days, similar to the current study [52]. They used a cross-correlation function to examine the association between the moving average of the mobility index and the time-lagged daily infected cases.…”
Section: Plos Onesupporting
confidence: 85%
“…Implementing distancing is only possible with public cooperation [ 9 , 10 ]. Such cooperation requires that people understand what they are being asked to do and why so that they adopt appropriate behaviors to help manage the pandemic [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…But it is difficult to get the reproduction number which can fit the epidemic transmission evolution perfectly in the real world. The deviation between theory and reality can be explained by the differences of individual behaviors 27 , 28 . The neglect of the micro heterogeneity may lead to misestimating the regional epidemic risks.…”
Section: Introductionmentioning
confidence: 99%